CHANGES IN THE MORPHOFUNCTIONAL PROPERTIES OF THE THYROID GLAND AND BLOOD INDICATORS DURING THE HYPOXIC PROCESS. - Khojiyev Dilmurod Yakhshiyevich; Karimova MuattarSharipovna (Scholar Express Journals, 2022)
Throughout a person's life, the thyroid gland (TG) is exposed to various adverse factors (environmental pollution, drug abuse, bad habits, malnutrition, etc.), which often lead to the development of its pathology. This necessitates the search for new effective means and methods for the prevention and treatment of thyroid dysfunction. During the hypoxic process, changes are observed not only in the morphological structures of the thyroid gland, but also in blood parameters. This process can also include periods of hypoxic state and oncogenesis in the perinatal period, on the basis of which this article analyzes studies of the effect of hypoxic conditions on the morphogenesis of the thyroid gland.
Keywords: thyroid gland; hypoxic state; oncogenesis; hormone